2019
DOI: 10.3390/resources8020063
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Energy Taxes to Climate Change Policy in the European Union (EU)

Abstract: Energy taxes are one of the main market-based tools directed toward mitigating climate change in the European Union (EU). Therefore, the aim of this article was to analyze whether energy taxes really contribute to the reduction of greenhouse gas (GHG) emissions and the successful implementation of climate change policy. Applying the Granger causality test on time series and using panel data analysis, the direct and indirect (via the reduction of fossil energy consumption (FEC) and energy intensity (EI), as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 75 publications
0
14
1
Order By: Relevance
“…Similarly, Gerlagh and Lise (2005) and Lin and Li (2011) did not find that environmental taxes were effective in reducing CO 2 emissions. Liobikienè et al (2019) also did not find that energy taxes influence GHG emissions in EU countries. Zhang (2016) also found that the impact of environmental regulations in China were low.…”
Section: Environmental Taxes and Environmental Degradationmentioning
confidence: 83%
“…Similarly, Gerlagh and Lise (2005) and Lin and Li (2011) did not find that environmental taxes were effective in reducing CO 2 emissions. Liobikienè et al (2019) also did not find that energy taxes influence GHG emissions in EU countries. Zhang (2016) also found that the impact of environmental regulations in China were low.…”
Section: Environmental Taxes and Environmental Degradationmentioning
confidence: 83%
“…Another instrument for sustainability and environmental deterioration are environmental protection policies [61]; among them are the implementation of taxes as demand policy measures to make consumers change their behaviors concerning the acquisition, use, and demand of polluting products and services [62]. Among the most controversial taxes and charges are those that affect the price of energy as they increase energy poverty and, with it, welfare; in Europe, it mainly affects Central and Eastern European countries [27,63].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies remain inconclusive about the use of energy tax to promote green innovation and less energy consumption [73,74]. In contrast, several studies reported no effect of environmental taxation on emissions [75,76].…”
Section: Review Of Past Studiesmentioning
confidence: 99%